Handover with network slicing in 5G networks - Sevim, Kübra. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2021., 2021)
5G suggests many advantages but these advantages bring some problems to be solved. Network Slicing is one of the key concepts that 5G introduces. Slicing enables having multiple isolated virtual networks on top of the same physical infrastructure. Thus, each slice can provide di↵erent services with diverse Quality of Service (QoS) requirements. In 5G, Software Defined Networking (SDN) and Network Function Vir tualization (NFV) are critical to support network slicing. In the literature, several problems of network slicing are studied. Two outstanding areas of focus are admission control and resource allocation. Most of the studies are on the Core Network resources although it is essential to investigate radio resource allocation in order to maintain an end-to-end isolation for slices. While there are considerable contributions around Radio Access Network (RAN) resource allocation, optimizing the throughput of the network is not fully achievable via admission control. In this thesis, we mainly focus on handover to maintain the usability and high utilization of the radio resources of the networks. When the number of users within one cell suddenly increases up to the limit of the base station, all of the incoming requests may not be handled and most of the users may su↵er from not being able to use the o↵erings of the slices that they demand. We develop an optimization problem to opti mize the radio resources and propose an heuristic to reach similar results by leveraging handover in considerably low computing times and with the simulation results we show that our heuristic can present solutions close to the optimal within a short time frame.
Keywords: 5G mobile communication systems.; Computer programs -- Network analysis.